Feasibility Study on Insect Pests Affecting the Growing of Naturally Colored Cotton Comparing with White Cotton in Thailand - Praparat Hormchan; Arunee Wongpiyasatid; Somchai Piyapuntawanon (Agriculture and Natural Resources, 2005)
Feasibility study of growing naturally colored cotton, Gossypium hirsutum, PM1and PM4 and Gossypium arboreum, PM2 along with white cotton, G.arboreum, PM3 comparing with the standard white G.hirsutum, SR60 was conducted from 2003-2004 at the National Corn and Sorghum Research Center, Pak Chong, Nakhon Ratchasima. RCB was used with 4 replicates, each with 5 rows of each variety. Data of insects were biweekly collected in the three middle rows for four consecutive times. In both years, the kinds and mean numbers of key pest were mainly leafhopper, Amrasca biguttula, and the plant bug, Megacoelum biseratense while the bollworm, Helicoverpa armigera was found in 2004 only. The 2003 and 2004 similar results revealed that the leafhoppers on PM1 and SR60 and those on PM2 and PM3 were not significantly different while all were significantly different from PM4. The average amounts of plant bug on every variety in both years were also found not to be significantly different from one another. Comparing the numbers of leafhopper between 2003 and 2004, they were significantly different at all varieties except PM2, while those of the plant bug on every variety did not significantly differ. As for the fiber analysis and % gin turn out, PM1 was found to have the acceptable qualities compared with the standard ranges of fiber determination as well as the commercial variety, SR 60.